PERANAN MOTIVASI SERTA DISIPLIN KERJA DALAM MENINGKATKAN PELAYANAN PUBLIK DI ERA OTONOMI DAERAH (STUDI PADA BPTP JAWA TIMUR DI KARANGPLOSO) - Willy Tri Hardianto (REFORMASI, 2011)
Human resources management is importan thing to organization existence so, this field, need a good human resources qualities. Motivation and work dicipline will created good qualities human resources that organization needed. Location on this research on BPTP Jawa Timur di Karangploso. This research is done by interview and observasi. A point on this research are motivation and work dicipline that aplicated on BPTP Jawa Timur di Karangploso is given direct influence and proofed by same change.